E-080 Endovascular stenting for idiopathic intracranial hypertension: a single-institution experience. (23rd July 2017) - Leonard, D; Haider, A; Thakur, R; Gottlich, C; Khan, U; Hise, J; Layton, K
Abstract : Introduction: The exact pathogenesis of idiopathic intracranial hypertension (IIH) is debated, though it is commonly believed to be due to some form of cerebrospinal fluid (CSF) outflow resistance or cerebral venous outflow abnormalities. The incidence of IIH is only 1-2 per 100, 000 with a much higher incidence in the subpopulation of obese women of reproductive age, up to 21 per 100, 000 women aged 15–44 years of age. The most common clinical presentations include headache, visual defects and papilledema, with the possibility of symptoms worsening to permanent vision loss. Treatment typically provides gradual improvements and is specifically oriented to preserve vision. Carbonic anhydrase inhibitors are considered the first-line of treatment, and failure to improve may indicate surgical intervention. Optic nerve sheath fenestration (ONSF) and CSF shunting procedures are the typically utilized surgical procedures. However, in patients with IIH who have evidence of dural sinus stenosis, dural sinus stenting (DSS) has become an interesting treatment method that has been studied little thus far. Methods: We present a single-center retrospective study of 22 cases of IIH that were refractory to medical treatment, treated with DSS over 35 months. Results: There were 22 females with a median age of 31 years. These patients, on average, suffered for 19.9 months prior to intervention and were followed for a median of 3 months. The most common symptoms encountered were headache (86.4%), visual obscurations (63.6%), and visual acuity changes (56.5%). Papilledema was encountered in only half of these patients. Acetazolamide was attempted to control the symptoms of IIH in 68.1% of patients, with little to no improvement. DSS was the first attempted surgical intervention in 90.4%, with only two patients having undergone ONSF and none receiving CSF shunting procedures. During cerebral venography, the pressure gradients across the stenosis averaged 14.5 mmHg, and the common locations for most significant stenosis were the transverse-sigmoid sinus junctions (54.5%) and the transverse sinuses (36.3%). There was a single case where stent placement was not successful from a femoral vein approach due to tortuosity resulting in a technical success rate of 95.5%. This outlier was eventually successfully treated with a jugular vein puncture. In patients receiving a stent, an immediate elimination of the pressure elevation and gradient was achieved in 100% of the cases. Two patients (9%) required placement of a second stent after follow-up revealed restenosis and development of a recurrent pressure gradient. There were no major or minor complications. Conclusion: IIH is an uncommon condition with presenting symptoms that are relatively nonspecific. Though medical therapy is first-line, an important subset of patients who experience IIH secondary to dural sinus stenosis are commonly refractory to medications alone. DSS is becoming a more commonly used therapy for treatment of this subpopulation. This study demonstrates that stenting is an effective procedure that can be performed with good technical success and minimal complications in specialized high volume stroke centers. Further research comparing DSS to ONSF and CSF shunting is required to determine the relative efficacies and long-term effects on symptom resolution and recurrence. Disclosures: D. Leonard: None. A. Haider: None. R. Thakur: None. C. Gottlich: None. U. Khan: None. J. Hise: None. K. Layton: None.